Indocyanine green dye angiography as an adjunct to assess indeterminate burn wounds: A prospective, multicentered, triple-blinded study - Wongkietkachorn, Apinut (J Trauma Acute Care Surg, 2019)
BACKGROUND: Clinical assessment of indeterminate burn wounds has been reported to yield poor accuracy, even when performed by burn experts. Indocyanine green (ICG) dye angiography has been found to be highly accurate in assessing burn depth, but there is still limited evidence of its use in indeterminate burn wounds. This study aims to compare the accuracy of ICG angiography to that of clinical assessment in assessing indeterminate burn wounds. METHODS: This is a prospective, multicentered, triple-blinded, experimental study. Participants were stable patients, admitted to the hospital with burn wounds of indeterminate depth. The burn wounds were clinically assessed by an attending plastic surgeon. ICG angiography was performed and evaluated by another surgeon. Tissue biopsies were obtained and sent for histological study to be assessed as the gold standard. RESULTS: In the 30 burn sites that were assessed, the accuracy of ICG angiography was 100.0%, compared with 50.0% for clinical assessment (p < 0.001). Clinical assessment yielded a sensitivity of 33.3% and specificity of 66.7%, while ICG angiography yielded both a sensitivity and specificity of 100.0%. Therefore, the number needed to treat for using ICG angiography in indeterminate burn wounds was two. CONCLUSION: Indocyanine green angiography yields a significantly higher accuracy than clinical assessment in indeterminate burn wounds. This intervention can, thus, be a useful tool to aid clinical judgment. TRIAL REGISTRATION: Thai Clinical Trials Registry, number TCTR20170821001. LEVEL OF EVIDENCE: Diagnostic test, level I.